American beauty - Spacey, Kevin; Bening, Annette; Birch, Thora ([S.l.] Dream Works SKG, 1999)
Lester Burnham, a depressed suburban father in a mid-life crisis, decides to turn his hectic life around after developing an infatuation for his daughter's attractive friend.
DVD
Kevin Spacey, Annette Bening, Thora Birch
Keywords: Feature Films